A robust superhydrophobic anti-icing/de-icing composite coating with electrothermal and auxiliary photothermal performances. (18th August 2022) - Zhao, Zehui; Chen, Huawei; Zhu, Yantong; Liu, Xiaolin; Wang, Zelinlan; Chen, Jichen
Abstract: Passive anti-icing and active anti-icing/de-icing were two major strategies to suppress icing on surfaces. Combining these two strategies and making full use of various energies can greatly improve anti-icing efficiency. In this study, a multifunctional anti-icing/de-icing coating with superhydrophobic passive anti-icing and electrothermal/photothermal active de-icing properties was proposed. Fluorinated epoxy resin and carbon/PTFE particles were used to prepare the multifunctional anti-icing/de-icing coating, which exhibited superhydrophobicity with water contact angle greater than 155° and conductivity higher than 40 S/m. The robust superhydrophobic property was demonstrated by repeated sandpaper abrasion and tape peeling tests. Moreover, both electricity and solar energy can be adopted for heating the surface and de-icing, showing efficient electrothermal/photothermal and anti-icing/de-icing properties. In addition, the synergistic icephobic mechanism was validated by characterizing the different freezing states of water droplets on surfaces: repelling droplets before freezing occurred, delaying icing during the freezing process and significantly reducing the ice adhesion after freezing via the self-generated micro-scale water film by heating. This study provided a new way to manufacture functional materials for practical anti-icing/de-icing applications. Graphical abstract: Image 1 Highlights: This multifunctional coating had both robust super-hydrophobic and electrothermal/photothermal properties. This coating showed excellent electro/photo-thermal properties and high-efficient anti-icing/de-icing behaviors. The synergistic icephobic mechanism of integrated passive and active anti-icing strategies was validated.